Relationship between Obstructive Sleep Apnea and Liver Abnormalities in Older Patients: A Cross-Sectional Study. (3rd January 2023) - Jin, Yong-Xu; Wang, Bi-ying; Wang, Xiao-li; Yu, Xing; Chen, Li-da; Yang, Yi-song; Huang, Jie-feng
Abstract : Background . Older age is a risk factor for obstructive sleep apnea (OSA), which is associated with the development of nonalcoholic fatty liver disease (NAFLD). We aimed to investigate the correlation between OSA and liver injury among older patients. Study Design . This is a cross-sectional study. Methods . Consecutive older (≥60 years) snoring patients were included. Subjects were divided into no OSA, mild OSA, moderate OSA, and severe OSA groups according to the apnea–hypopnea index (AHI) and were also separated into liver injury and nonliver injury groups based on liver function. Logistic regression analysis was applied to analyze the independent risk factors for liver injury. Results . We studied 227 patients (155 male, 72 female). The prevalence of liver injury exhibited an increasing trend among groups with mild-to-severe OSA. In addition, body mass index, AHI, and TG showed significant differences between the liver injury and nonliver injury groups. Logistic regression analysis revealed that AHI and TG were the major contributing factors for liver injury in older patients (adjusted odds ratio [OR] = 1.055, p = 0.013, and OR = 1.485, p = 0.039, respectively). Conclusions . Older patients with OSA have an increased risk of liver injury and NAFLD, and sleep apnea and high TG are important factors in contributing to the development of liver injury.